2003
DOI: 10.1016/s1631-0691(03)00070-2
|View full text |Cite
|
Sign up to set email alerts
|

Soil macroinvertebrates as indicators of pollution by heavy metals

Abstract: A broad range of soil pollutants were found to decrease with distance from a zinc smelter from 35 000 to 77, 8270 to 40 and from 190 to less than 1 ppm for zinc, lead and cadmium, respectively. Along this gradient, observed species richness of soil macro-organisms seemed to be more affected by the land-use type than by soil pollution -minimum in crops (21), maximum in woody sites (126). IndVal index allowed isolation of 21 indicator species from the 339 morphospecies identified. Most of these indicator species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 17 publications
0
12
0
2
Order By: Relevance
“…The slow down of the organic matter degradation in soils around Umicore can be induced by the higher contamination levels and/or by the more frequent waterlogging in this area. It was shown that high concentrations of Cd, Pb and Zn around the two smelters strongly affected the ecosystem functioning by reducing the biodiversity and especially the terrestrial macroinvertebrates (Grelle et al 2000;Nahmani and Rossi 2003) and thus disturbing the carbon cycle. Waterlogging of the soils around Umicore is related to an alluvial characteristic and to the presence of the ground water rising at the soil surface during the wet season and especially in winter.…”
Section: Physico-chemical Characteristics Of Urban Soilsmentioning
confidence: 99%
“…The slow down of the organic matter degradation in soils around Umicore can be induced by the higher contamination levels and/or by the more frequent waterlogging in this area. It was shown that high concentrations of Cd, Pb and Zn around the two smelters strongly affected the ecosystem functioning by reducing the biodiversity and especially the terrestrial macroinvertebrates (Grelle et al 2000;Nahmani and Rossi 2003) and thus disturbing the carbon cycle. Waterlogging of the soils around Umicore is related to an alluvial characteristic and to the presence of the ground water rising at the soil surface during the wet season and especially in winter.…”
Section: Physico-chemical Characteristics Of Urban Soilsmentioning
confidence: 99%
“…From this point of view, insect larvae have many useful properties which make them sentinel organisms in freshwater biomonitoring programs (Hare and Tessier 1998;Nahmani and Rossi 2003). Goodyear and McNeill (1999) defined insect larvae as organisms, commonly found in freshwaters of all types, able to tolerate and accumulate moderate metal concentrations.…”
mentioning
confidence: 99%
“…Logo, embora seja evidente que há diferença entre as áreas contaminadas e não contaminadas por chumbo, a abundância e em alguns casos, a riqueza, parece ser influenciada mais fortemente pela cobertura vegetal e as condições abióticas oriundas dela, do que pela poluição. Esta ideia corrobora com Nahmani & Rossi (2003), em seu estudo em área contaminada por zinco, cádmio e chumbo na França, em que se observou maior riqueza de grupos em áreas de pastagens contaminadas em relação a outros usos de solo em áreas não contaminadas.…”
Section: Resultados E Discussõesunclassified